Preliminary Study on National Road Condition of Ambon City, Indonesia - Hamkah, Robert Sihotang, Vera Th. C. Siahaya (International Journal of Advanced Science and Technology, 2020)
The national road in Ambon City connects Pattimura Airport with Yos Sudarso Port having double access with parallel road conditions. Some road segments are not continuous like Jalan A.M. Sangadji and Jalan Rijali, have two lanes but are still one-way. This study aims to review the capacity of the two national road segments in Ambon City based on the existence of each road section according to LHR conditions, side friction, and continuous road requirements. According to the scientific stages, the study was carried out in a structured and systematic manner using data from field observations and the latest secondary data from data sources in the BPJN XVI Ambon work unit covering Down Road and Upper Road). The study results were selected three alternative national road access. The first alternative, using down national road access with recommendations for reclamation of the Pantai Mardika road section, connecting six roads each: Yos Sudarso, Pala, Pantai Mardika, Pantai Batu Merah, Ongko Liong, and Jalan Sultan Hasanuddin. The second alternative uses upper national road access with recommendations for flyover development, connecting six roads: Pelabuhan, A.M. Sangadji, Diponegoro, Ahmad Yani, Rijali, and Sudirman. The Third alternative, using parallel national road access between down and upper national road for current conditions, with recommendations on traffic engineering and handling of several road sections to be continuous. Keywords: National road; Ambon City; existing conditions; segment; roads